2018
DOI: 10.2147/cmar.s167071
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of carcinoma-associated fibroblasts and tumor-associated macrophages in nasopharyngeal carcinoma

Abstract: PurposeTumor stroma cells play an important role in the carcinogenesis and progression of cancer. The aim of the present investigation was to explore the predictive role of carcinoma-associated fibroblasts (CAFs) and tumor-associated macrophages (TAMs) in nasopharyngeal carcinoma (NPC).Patients and methodsThe densities of CAFs and TAMs were measured by immunohistochemistry staining for α-smooth muscle actin (α-SMA), CD68, and CD163 in two sets of tissue microarrays including 260 pretreatment NPC tissues, that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 51 publications
1
44
0
Order By: Relevance
“…There are evidence suggesting that EBV‐infected NPC cells interacted with TME components to facilitate metastasis. An increased presence of Foxp3 + Treg cells and CD68 + tumor‐associated macrophages (TAMs) has been found in EBV‐positive NPC specimens and associated with poor prognosis . Another recent study has revealed an interacting loop between NPC cells and TAMs in driving NPC metastasis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are evidence suggesting that EBV‐infected NPC cells interacted with TME components to facilitate metastasis. An increased presence of Foxp3 + Treg cells and CD68 + tumor‐associated macrophages (TAMs) has been found in EBV‐positive NPC specimens and associated with poor prognosis . Another recent study has revealed an interacting loop between NPC cells and TAMs in driving NPC metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…An increased presence of Foxp3 + Treg cells and CD68 + tumor-associated macrophages (TAMs) has been found in EBV-positive NPC specimens and associated with poor prognosis. 13 Another recent study has revealed an interacting loop between NPC cells and TAMs in driving NPC metastasis. In plethora of tumor microenvironmental cell types, cancer-associated fibroblasts (CAFs) have involved as one of the most promising targets owing to their abundant presence and functional significance in various tumor entities, including multiple myeloma, oral cancer, and gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar vein, Yu et al (2018) also demonstrated the use of αSMA expression in CAFs, as well as CD163 expression on tumour-associated macrophages (TAMs), as independent predictors of survival in NPC prognostication using tissue microarrays [61]. To date, this is the only study linking CAFs and TAMs in NPC progression and survival, however studies in other cancers describe a crosstalk between resident CAFs and TAMs in the TME.…”
Section: The Role Of Cafs In the Npc Tumour Microenvironmentmentioning
confidence: 89%
“…In HNSCC, macrophages promote cell migration, invasion and lymph node metastasis in in vitro and in vivo models, and are associated with worse outcome in patients (53,57,58). Moreover, studies show the correlation between the density of CAFs and TAMs with poor outcome in HNSCC (59,60). Furthermore, one study reported that protumorigenic macrophage polarization is promoted in HNSCC tumors with high lactic acid concentrations (61).…”
Section: Discussionmentioning
confidence: 99%